Hydraulic investigation of the H-type floating breakwater - Teh, H.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
Floating breakwaters are commonly used for wave protection of onshore and offshore facilities in the last decade. The majority of the floating breakwaters developed in the past are solid-type structures that have fixed drafts and may be highly reflective to the incoming waves. In this study, the H-type floating breakwater is proposed to serve as a wave attenuator instead of a wave reflector. The buoyancy of the breakwater is controlled by the placement of sandbags in the chamber embedded within the main body of the structure. The study aims to investigate the hydraulic properties of the H-type floating breakwater in random waves via a physical modeling. The hydraulic characteristics of the breakwater are quantified by the reflection and transmission coefficients as well as the energy dissipation coefficient. The experimental results have shown that the H-type floating breakwater is hydraulically efficient and provides high wave attenuation capability when subjected to short-period waves. Â© 2014 IEEE.